2021
DOI: 10.3390/plants10050872
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Rhizobacteria Isolated from Citrus Rhizosphere for Biological Control of Citrus Dry Root Rot

Abstract: Citrus trees face threats from several diseases that affect its production, in particular dry root rot (DRR). DRR is a multifactorial disease mainly attributed to Neocosmospora (Fusarium) solani and other several species of Neocosmospora and Fusarium spp. Nowadays, biological control holds a promising control strategy that showed its great potential as a reliable eco-friendly method for managing DRR disease. In the present study, antagonist rhizobacteria isolates were screened based on in vitro dual culture bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…Some diseases are not caused by a single bacterium. For example, citrus dry root rot is a multifactorial disease mainly attributed to Neocosmospora solani as well as other species of Neocosmospora and Fusarium spp (Ezrari et al, 2021). Riaz et al (2020) identified Neocosmospora as a new pathogen of potato stem rot.…”
Section: Discussionmentioning
confidence: 99%
“…Some diseases are not caused by a single bacterium. For example, citrus dry root rot is a multifactorial disease mainly attributed to Neocosmospora solani as well as other species of Neocosmospora and Fusarium spp (Ezrari et al, 2021). Riaz et al (2020) identified Neocosmospora as a new pathogen of potato stem rot.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of action determining the success of biocontrol are complex, which, to some extent, may explain the limited effectiveness of biocontrol against plant diseases in field crops. In this case, the screening of these BCAs can be achieved by phenotype-based screenings by evaluating pathogen growth by dual culture assay or by volatile antifungal compounds (VOCs) or by marker-based screening: secretion of antimicrobial metabolites (antibiosis via bacterial supernatant), the secretion of cell-wall-degrading or screening bacteria with specific inhibitory mechanisms [ 76 , 131 ].…”
Section: Bcas Modes Of Actionmentioning
confidence: 99%
“…T h e pu r e -c u l t u r e m e t h o d wa s u s e d t o i s o l a t e microorganisms from rhizosphere soil (Jogaiah et al, 2013;Ezrari et al, 2021). The rhizosphere soil collected in Section 2.1 was used to isolate rhizosphere microorganisms.…”
Section: Isolation and Identification Of Rhizosphere Microorganismsmentioning
confidence: 99%
“…In a field experiment, inoculation with two antagonistic bacteria (Pseudomonas and Bacillus) in rhizospheric soil of tomato could stimulate its defense against R. solani (Kwak et al, 2018). Two rhizobacterial isolates Bacillus subtilis K4-4 and GH3-8 could completely suppress citrus dry root rot disease caused by Neocosmospora solani in greenhouse trials (Ezrari et al, 2021). The relationship between C. sativus rhizosphere microorganisms and phenology has been revealed by highthroughput sequencing (Ambardar et al, 2016); however, the relationship between the rhizosphere microbiome and disease resistance is unclear.…”
Section: Introductionmentioning
confidence: 99%